Vulnerability to hunger: Improving food crisis responses in fragile states - Colin Andrews; Margarita Flores (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The paper examines the imperative for improved classification and analysis of food crises in different fragile contexts. Recognizing the persistence and protracted nature of food crises, the paper questions how prevention and response mechanisms could be improved to help decisionmakers better address the underlying causes of vulnerability and hunger. The paper draws on case study information to examine real life opportunities and constraints in applying a recently developed food security classification system, named the analytical frameworks at country level, the Integrated Food Security Phase Classification (IPC). Developed originally in Somalia, this classification framework is now being applied in a range of country contexts within and outside of Africa by national governments, UN agencies, donors and NGO organizations. The paper draws on early applications of the IPC to consider opportunities and constraints in the application of common classification systems, taking into account issues of institutional adaptation, methodologies, data and analysis.
Keywords: O1; O19; 330; food security; humanitarian assistance; complex emergencies; Nahrungsmittelversorgung; Unterernährung; Katastrophenhilfe; Staatskrise